2020
DOI: 10.1111/lang.12415
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Gesture on Second Language Pronunciation: An Exploratory Study of Handclapping as a Classroom Instructional Tool

Abstract: In this study, we examined the efficacy of gestures for the acquisition of L2 segmental phonology. Despite teachers’ frequent use of gestures in the classroom to teach pronunciation, the field lacks empirical support for this practice. We attempted to fill this gap by investigating the effects of handclapping on the development of L2 Japanese segmentals (long vowels, geminates, and moraic nasals). We assigned L1 English university students in beginning Japanese courses to one of two groups where they practiced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…However, the experimental task of repeating a string of words for 10 minutes without any clear sentential meaning lacked ecological validity and may have led to boredom. Finally, an experimental study by Baills, Zhang, and Prieto (2018) found that handclapping to the rhythmic structure of words improved L2 pronunciation and a recent experimental study in a classroom setting by Iizuka, Nakatsukasa, and Braver (2020) found that hand-clapping benefitted the perception of segmental phonology, suggesting a potential role for providing rhythmic support in the learning of pronunciation.…”
Section: Songs and Singing For L2 Pronunciation Learningmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the experimental task of repeating a string of words for 10 minutes without any clear sentential meaning lacked ecological validity and may have led to boredom. Finally, an experimental study by Baills, Zhang, and Prieto (2018) found that handclapping to the rhythmic structure of words improved L2 pronunciation and a recent experimental study in a classroom setting by Iizuka, Nakatsukasa, and Braver (2020) found that hand-clapping benefitted the perception of segmental phonology, suggesting a potential role for providing rhythmic support in the learning of pronunciation.…”
Section: Songs and Singing For L2 Pronunciation Learningmentioning
confidence: 94%
“…Further research will therefore be needed to explore the role of individual differences in L2 phonological learning, not only under the conditions examined here but also in other populations and under other phonological learning conditions. For example, rhythmic and melodic abilities could be analyzed separately to see if there are language-dependent preferences in terms of sound properties, as in the study by , and see Iizuka et al (2020).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…It is useful to turn to a multimodal framework for the analysis of embodied modes, since the pre‐existing research on embodied modes stems primarily from the CA framework, in which researchers have examined how talk develops through interaction, typically with an emphasis on talk (Goodwin, 1986; ten Have, 2007). CA studies have articulated how teachers and students use predetermined gestures to teach and learn vocabulary (Belhiah, 2013; Regalla & Peker, 2015; Schneider & Evers, 2009) and pronunciation (Iizuka et al, 2020; Smotrova, 2015). Although this research has illuminated how language learners navigate their semiotic resources, little is known about how they use their bodies in nonscripted ways as they express themselves in the L2.…”
Section: Theoretical Framework: Multimodalitymentioning
confidence: 99%
“…For example, in an intensive English university class, the instructor's use of deliberate nodding and tapping to emphasize prosody was imitated by the students (Smotrova, 2015). Likewise, in a university Japanese course, students who clapped their hands while learning pronunciation features (i.e., segmentals) performed more accurately on memory recall tests than students who did not clap (Iizuka et al, 2020).…”
Section: Literature Review: Embodiment In L2 Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation